OVERWEIGHT IN SCHOOL-AGE CHILDREN AND ITS RISK FACTORS - Pratiwi Hariyani Putri; Catur Wulandari; Sa'bania Hari Raharjeng; Dini Setiarsih; Anugrah Linda Mutiarani; Mery Indartiningsih; Choirinah Fadhilatur Rohmah; Aisyah Nur Safitri; Vera Desianti Ika Haryono (Universitas Airlangga, 2024)
Introduction: According to data from the Basic Health Research in 2018, the prevalence of overweight and obesity among children in East Java Province was 24.27%. This prevalence is still higher than the national average. Aims: This study aims to analyze the risk factors for overweight in school-age children in Tawangsari Village, Sidoarjo Regency, East Java Province. Methods: This study used a case-control design and involved 132 school-age children at 1 and 3 Tawangsari State Elementary Schools, Sidoarjo Regency. The respondents were divided into two groups, namely case and control. The data were analyzed using multiple logistic regression with a significance level at 0.05. Result: The results of the multivariate analysis suggested that sedentary behavior (p = 0.002; Exp(B) = 8.340), sugar intake (p = 0.000; Exp(B) = 9.125) and vegetable and fruit intake (p = 0.007; Exp(B) = 20.643) were significant variables (p < 0.05). Conclusion: School-age children with low levels of physical activity were found to be 8.34 times more likely to be overweight compared to those with high levels of physical activity. In addition, excessive sugar intake and inadequate consumption of vegetable and fruit were associated with a higher likelihood of being overweight in school-age children. However, dietary diversity is not a risk factor for overweight in school-aged children.